Binding mechanism of arsenate on rutile (1 1 0) and (0 0 1) planes studied using grazing-incidence EXAFS measurement and DFT calculation. (March 2015) - Zhang, Meiyi; He, Guangzhi; Pan, Gang
Graphical abstract: Highlights: Structure and stability of arsenate on rutile (1 1 0) and (0 0 1) surfaces were studied. Polar angles of arsenate on (1 1 0) surface were smaller than that on (0 0 1) surface. Orientational polar angle of arsenate was related to its adsorption stability. (1 1 0) surface displayed a higher affinity toward arsenate than (0 0 1) surface. Abstract: Characterization of contaminant molecules on different exposed crystal planes is required to conclusively describe its behavior on mineral surfaces. Here, the structural properties and relative stability of arsenate adsorbed on rutile TiO2 (1 1 0) and (0 0 1) surfaces were investigated using grazing-incidence extended X-ray absorption fine structure (GI-EXAFS) spectra and periodic density functional theory (DFT) calculation. The combined results indicated that arsenate mainly formed inner-sphere bidentate binuclear (BB) and monodentate mononuclear (MM) complexes on both surfaces, but the orientational polar angles of arsenate on the (1 1 0) surface were commonly smaller than that on the (0 0 1) surface for the two adsorption modes. The DFT calculation showed that the (1 1 0) plane had a higher affinity toward arsenate than the (0 0 1) plane, suggesting that, for a given adsorption mode (i.e., MM or BB structure), a small polar angle was more favorable for arsenate stabilized on the rutile surfaces.